Current and future interactions between nature and society - Klatt, Brian; Ometto, Jean Pierre; García Marquez, Jaime; Baptiste, María Piedad; Instituto Alexander von Humboldt; Acebey, Sandra Verónica; Guezala, María Claudia; Mastrangelo, Matias Enrique; Pengue, Walter Alberto; Blanco, Mariela Verónica; Gadda, Tatiana; Ramírez, Wilson; et al.
One hundred per cent of the natural units of analysis will continue to be negatively affected, with a concomitant decrease in natures contributions to people, given current trends (business as usual), though the magnitude and exact mechanism of the individual drivers will vary by driver and unit of analysis (established but incomplete){5.4}. For example, tropical moist and dry forest and coastal mangroves will continue to exhibit a decline due to land use change regardless of the scenarios considered, but different local factors (agriculturalization and urbanization, respectively) will be involved (well established) {5.4.1, 5.4.11}. Additionally, some drivers will affect units of analysis differently. Empirical evidence indicates differential effects of climate change: boreal forest is extending northward {5.4.2}, while tundra is diminishing in land area (established but incomplete) {5.4.3}. Thus, some drivers, and their relative roles, will need to be further refined on a local scale and with respect to their proximate factors.2. Multiple drivers will act in synergy and further produce biodiversity loss and impact nature?s contributions to people in most of the units of analysis for the Americas (established but incomplete){5.4}. Climate change, combined with other drivers, is predicted to account for an increasingly larger proportion of biodiversity loss in the future, in both terrestrial and aquatic ecosystems {5.3}. Forest fragmentation, climate change and industrial development increase risk of biodiversity and nature?s contributions to people loss i.e. dry forest unit of analysis {5.4.1.2}. Predictions on invasive species and climate change indicates an increase in habitable areas and their potential impacts on different units of analysis {5.3}.3. Changes in temperature, precipitation regime and extreme climate events are predicted to impact all units of analysis in the Americas (well established) {5.4}. Climate change and the potential impacts on tropical dry forests by changing the frequency of ...